The Impact of Positive Psychology Interventions in Increasing Learning Satisfaction: Dampak Intervensi Psikologi Positif dalam Meningkatkan Kepuasan Belajar - Nurmala, Eka; Baihaqi, Baihaqi; Hamidi, Nazilul; Saleh, Sahar; Sumarta, Ryan Puby (PT. Alpha Trianguli Australis, 2025)
Learning satisfaction is a main factor determining students' academic success and psychological well-being. Positive psychology is a branch of psychology that emphasizes strengthening positive aspects in individuals, such as positive emotions, happiness, and optimism. This study uses the Systematic Literature Review (SLR) method to identify and analyze relevant literature on positive psychology interventions in improving learning satisfaction. The results of this study are: 1) Positive psychology interventions have a significant impact on students' learning satisfaction; 2) Gratitude exercises, mindfulness, happiness interventions, strength-based approaches, and social support be effective in enhancing more positive learning experiences; and 3) The implications of this study emphasize the importance of integrating positive psychology strategies into the curriculum and education policies to create a healthier learning environment and support student well-being.